Cladribine: from the bench to the bedside –– focus on hairy cell leukemia. Issue 5 (1st October 2004) - Greyz, Natalya; Saven, Alan
Cladribine is an adenosine deaminase-resistant deoxyadenosine analog with a unique mechanism of action. It is directly toxic towards both resting and proliferating human lymphocytes and monocytes. The development of this compound into clinical practice best exemplifies rational drug development and the success of translational research. Cladribine is well established as first-line treatment for hairy cell leukemia, inducing an overall response rate of 75––100%, with the majority being complete responses following only a single 7-day treatment course. The 9-year overall survival for hairy cell leukemia is currently 97%. Cladribine has also proven useful in the treatment of a variety of other hematologic malignancies, and its current place in the oncologic therapeutic armamentarium, as well as in potential areas of development, are outlined.